Arsenic Exposure, Blood DNA Methylation, and Cardiovascular Disease. Issue 2 (8th July 2022) - Domingo-Relloso, Arce; Makhani, Kiran; Riffo-Campos, Angela L.; Tellez-Plaza, Maria; Klein, Kathleen Oros; Subedi, Pooja; Zhao, Jinying; Moon, Katherine A.; Bozack, Anne K.; Haack, Karin; Goessler, Walter; Umans, Jason G.; et al.
Abstract : Background: Epigenetic dysregulation has been proposed as a key mechanism for arsenic-related cardiovascular disease (CVD). We evaluated differentially methylated positions (DMPs) as potential mediators on the association between arsenic and CVD. Methods: Blood DNA methylation was measured in 2321 participants (mean age 56.2, 58.6% women) of the Strong Heart Study, a prospective cohort of American Indians. Urinary arsenic species were measured using high-performance liquid chromatography coupled to inductively coupled plasma mass spectrometry. We identified DMPs that are potential mediators between arsenic and CVD. In a cross-species analysis, we compared those DMPs with differential liver DNA methylation following early-life arsenic exposure in the apoE knockout (apoE −/− ) mouse model of atherosclerosis. Results: A total of 20 and 13 DMPs were potential mediators for CVD incidence and mortality, respectively, several of them annotated to genes related to diabetes. Eleven of these DMPs were similarly associated with incident CVD in 3 diverse prospective cohorts (Framingham Heart Study, Women's Health Initiative, and Multi-Ethnic Study of Atherosclerosis). In the mouse model, differentially methylated regions in 20 of those genes and DMPs in 10 genes were associated with arsenic. Conclusions: Differential DNA methylation might be part of the biological link between arsenic and CVD. The gene functions suggest that diabetes might represent a relevant mechanism for arsenic-related cardiovascular risk in populations with a high burden of diabetes.